Correlation Analysis of Vaginal Microbiome Changes and Bacterial Vaginosis Plus Vulvovaginal Candidiasis Mixed Vaginitis Prognosis - Xiao, Bingbing; A, Disi; Qin, Hanyu; Mi, Lan; Zhang, Dai (Frontiers in Cellular and Infection Microbiology, 2022)
Mixed vaginitis is the result of the simultaneous presence of different pathogenic processes mediated by at least two types of vaginal pathogens. Among the various types of mixed vaginitis presentations, bacterial vaginosis (BV) plus vulvovaginal candidiasis (VVC) presents to be the most prevalent form. Mixed vaginitis affects the health of women of all ages worldwide. However, few studies have focused on clinical manifestations, pathogenesis, diagnostic criteria, or therapy of mixed vaginitis. We recruited 48 symptomatic patients with clinical diagnoses of VVC complicated with BV, they were treated with oral metronidazole combined with local clotrimazole and followed to assess the drug efficacy and vaginal microbiome alterations before and after treatment. The vaginal microbiome in BV+VVC mixed vaginitis patients was altered significantly after the combined drug treatment within a unique form different from a simple overlay mode of BV and VVC, the key bacteria including Gardnerella and Atopobium, Lactobacillus. The combined drug therapy for the mixed vaginitis in this study was effective and enhanced treatment for BV may be more favorable because of more difficulty in dealing with BV according to the treatment outcome. The abundance of Lactobacillus in patients with mixed vaginitis affects the recovery of the vaginal microbiome as well as the prognosis, and the abundance should be actively restored. This is the first study to investigate the composition, diversity, and other characteristics of the vaginal microbiome in patients with BV+VVC mixed vaginitis before and after drug treatment, our results provide clues to improving the cure rate and reducing recurrences.